Áreas de preservação permanente (APPs) no Brasil e na França: um comparativo - Sidnei Luís Bohn Gass; Roberto Verdum; Jeannine Corbonnois; François Laurent (Confins)
The legislation that defining the Permanent Preservation Areas (APPs), related to the riparian forests in Brazil, has undergone numerous changes between the years 1934 and 2012. The focus of the discussions that occurred is in duality preservation versus agricultural production, which takes as part of the truth, stop using some areas, means reducing the amount of production, generating a discussion based on a highly economical aspect. In France it is the code ratified by the law of 2003 (Law n° 2003-590 of July 2, 2003, dubbed the law "urbanisme et habitat") which provides for the protection of areas considered natural. It includes all the provisions designed to protect the environment, particularly those relating to the conservation of fauna and flora, in addition to landscape protection. This article is mainly aimed to compare the treatment of APPs in Brazil and France, bringing to the discussion that may contribute to their understanding and the different forms of management of these areas in both countries. The purpose is also to determine the issues and disputes relating to environmental protection. In Brazil, they are treated better in the perspective of the protection of natural ecosystems. In France, in view of the occupation history of space by human societies, issues and disputes are established in terms of recovery and renaturation of the environment, including the logic of environmental protection. Thus, the article presents a historical context of APPs in the two countries concerned, from the existing legislation. It also presents the practical application of legislation, thus bringing new elements to the discussion. Comparing the legislation model and its application, on the theme of APPs in Brazil and France, it is observed that there are different aspects of the environment, environmental legislation and management needs associated with the reality of each country, which are result of historical processes of occupation and land use. It is, finally, a question: what are the similarities between the management models of both countries? The differences also are numerous, because they depend on the perception / image of people in their communities, changes in attitudes and changes in attitudes, the lack of data, etc.